Invited Paper: On the Correlation between Electron Polarizability of Molecular Core and its Input into Optical Anisotropy. Issue 1 (June 2014) - Harmata, P.; Herman, J.; Czerwiński, M.; Chojnowska, O.; Kula, P.
Abstract Highly birefringent liquid crystals have been desired recently by many applications in visible, infrared and recently other spectral regions such as THz and GHz as a active medium for various devices fabrication. For the broad temperature range of the nematic phase mixture formulation several structurally differentiated classes of nematogenes are necessary. Only structurally diversified compounds enable creation of proper eutectic composition necessary either for stable nematic phase formation as well as for destabilization of solid and smectic phase in some cases. The molecular design of highly birefringent compounds is usually based on the combination of molecular core design, polar groups and terminal flexible chain selections. The highest influence on the optical anisotropy has the proper selection of rigid core, since its intrinsic electron polarizability and order parameter of LC have direct relation with the birefringence value. Due to high melting points, nonfunctionalized rigid core do not exhibit any mesomorphic properties or for some long cores only monotropic ones. In this work we synthesized the most common and widely used rigid core systems, mainly tolane and phenylethynyltolane derivatives, and measured temperatures of virtual nematicisotropic transitions. Second part of the work is related to determination of available optical anisotropy for prepared cores, measured and extrapolated from its mixtures with host nematic mixture. The obtained values are compared with electron polarizability anisotropies calculated numerically using state of the art DFT numerical algorithms. The correlation between optical anisotropy of molecular core and anisotropy of electronic polarizability will be deeply analyzed and discussed.